A Queer Little Book: An Examination of the Reception of Peter Damian's Liber Gomorrhianus by the Papacy and the Canonical Tradition - Olsen, Robert J. (Viator, 2018)
Abstract In the early years of the Gregorian Reform, Peter Damian composed a letter to the newly enthroned Pope Leo IX. Its subject was the issue of sexual immorality amongst the clergy of the church- though not on the question of clerical marriage, which may be expected, but instead on the issue of sodomy. This letter, often titled the Liber Gomorrhianus, was the first dedicated treatment of the subject in the history of the church. Damian advocated for a broadening of the definition of sodomy to include all samesex acts as well as masturbation (a schema already partially begun by Burchard of Worms several decades before), and argued that any clergyman who committed such deeds ought to be removed from office. Utilizing twenty separate canons on the topic of sodomy or related topics in nearly thirty different collections from Regino of Prüm to Gratian, the influence of Damian's ideas is examined herein. Did his new approach to sodomy have precedents in former canonical collections-and did any of the canonists after Damian utilize his ideas? After an analysis of these canons, it seems clear that Damian had little impact on the canonists' views on the subject of sodomy, despite his virulent opposition to the practice. Instead, the canonists continue mostly unaltered with the tradition of those canonists who came before Damian's Liber.